2020
DOI: 10.3390/brainsci10050273
|View full text |Cite
|
Sign up to set email alerts
|

Cadence Modulation in Walking and Running: Pacing Steps or Strides?

Abstract: A change in cadence during walking or running might be indicated for a variety of reasons, among which mobility improvement and injury prevention. In a within-subject study design, we examined whether walking or running cadences are modulated best by means of step-based or stride-based auditory pacing. Sixteen experienced runners walked and ran on a treadmill while synchronizing with step-based and stride-based pacing at slow, preferred and fast pacing frequencies in synchronization-perturbation and synchroniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…These results are consistent with previous results on walking behavior, demonstrating that instructing participants to move to the beat elicited slower and shorter strides than when instruction was absent 33 . They are also in accordance with earlier findings indicating that, when compared with stride‐based pacing, step‐based pacing leads to more stable auditory–motor coordination in both walking and running 52 . Consequently, although a number of studies demonstrated that auditory–motor coupling improved performance in motor tasks, 11,12,18 our findings suggest that entrainment as such does not necessarily speed up recreational runners or lengthen their steps, as this seems to depend on the presence/absence of instruction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with previous results on walking behavior, demonstrating that instructing participants to move to the beat elicited slower and shorter strides than when instruction was absent 33 . They are also in accordance with earlier findings indicating that, when compared with stride‐based pacing, step‐based pacing leads to more stable auditory–motor coordination in both walking and running 52 . Consequently, although a number of studies demonstrated that auditory–motor coupling improved performance in motor tasks, 11,12,18 our findings suggest that entrainment as such does not necessarily speed up recreational runners or lengthen their steps, as this seems to depend on the presence/absence of instruction.…”
Section: Discussionsupporting
confidence: 93%
“…33 They are also in accordance with earlier findings indicating that, when compared with stride-based pacing, step-based pacing leads to more stable auditory-motor coordination in both walking and running. 52 Consequently, although a number of studies demonstrated that auditory-motor coupling improved performance in motor tasks, 11,12,18 our findings suggest that entrainment as such does not necessarily speed up recreational runners or lengthen their steps, as this seems to depend on the presence/absence of instruction. The fact that instructed entrainment did not lead to an increase in speed and step length, whereas spontaneous entrainment did, might be related to the idea that instruction results in more goal-directed behavior, as such directing the focus to the achievement of entrainment and suppressing possible arousal effects caused by the auditory accompaniment.…”
Section: Discussionmentioning
confidence: 57%
“…Second, real-time feedback of gait parameters such as cadence and contact times derived from inertial sensors is often provided visually on a watch, looking at which interferes with running [ 15 , 22 ]. Auditory instructions or feedback on gait parameters, for example through auditory pacing [ 23 ] or sonification [ 24 , 25 ], is therefore preferable [ 26 ]. Third, previous research indicated that runners dislike carrying their phone and would prefer using an all-in-one device [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of perturbations to the auditory stimuli used in the majority of published literature to date has been selected somewhat arbitrarily and discordantly: phase shifts of 50 ms ( Chen et al, 2006 ); 60° ( Roerdink et al, 2009 ; Nijs et al, 2020 ); 100 ms ( Wright et al, 2014 ); and 15% of step cycle ( Khan et al, 2020 ). In the present study, we perturbed the metronome cues based on each individual’s step time variability (measured in standard deviations).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the extent to which footfall rhythm influences stability may also depend on the rhythm perception ability of the participants [instructing poor rhythm perceivers to synchronize could incur instability ( Ready et al, 2019 )] and the magnitude of perturbations ( Dotov et al, 2019 ). As more studies including rhythm perturbations are now emerging ( Krasovsky et al, 2013 ; Wright et al, 2017 ; Geerse et al, 2020 ; Khan et al, 2020 ; Nijs et al, 2020 ), it is timely to identify the governing principles and detail the involvement of dynamic stability during movement adaptation to rhythm perturbations: hence addressing the fundamental question of how footfall rhythmicity interacts with whole-body balance during walking.…”
Section: Introductionmentioning
confidence: 99%